POLÍTICAS PARA A EDUCAÇÃO PROFISSIONAL E A ARTICULAÇÃO ENTRE O ENSINO PROFISSIONAL E O ENSINO MÉDIO... | Policies for Professional Education and articulation between the Vocational Education and Secondary Education... (Trabalho & Educação, 2016)
This Thesis focuses on Integrated Education, that is the education which articulates Vocational Education with Secondary Education. On the one hand, it is analyzed the easy side as well as the difficulties found in integrating the two types of education. On the other, it is discussed the importance of such integration in the promotion of the quality of education in the institution in which the research was done. The loci of research were two campi of a school which belongs to the Federal Net of Vocational, Scientific and Technological Education in the State of Minas Gerais. Those two campi present different start up times and since the enactment of the Decree number 5.154/2004 have been working on the integration. It is worth mentioning that this thesis is based on a bibliographical research carried out throughout the investigation. As to the methodology used...___Esta Tese tem, por objeto de estudo, o Ensino Integrado, que busca fazer a articulação entre a Educação Profissional Técnica de Nível Médio e o Ensino Médio. Nessa perspectiva, analisaram-se, por um lado, as facilidades e as dificuldades encontradas para se integrar a referida modalidade de educação com o mencionado nível de ensino. Por outro, investigou-se a importância dessa integração para promover a qualidade do ensino, na instituição pesquisada. Os loci desta Pesquisa foram duas unidades de uma Instituição da Rede Federal de Educação Profissional, Científica e Tecnológica de Minas Gerais, que possuem tempos de implantação diferentes e, desde a veiculação do Decreto n. 5.154/2004, vêm procurando assegurar essa integração. Ressalta-se que, no início e no decorrer desta investigação, foi realizada uma pesquisa bibliográfica que deu embasamento a este estudo. No que tange, mais especificamente, à metodologia, foi desenvolvida...